2018
DOI: 10.1108/ijccsm-01-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

The study of potential evapotranspiration in future periods due to climate change in west of Iran

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
(27 reference statements)
2
8
0
Order By: Relevance
“…The prediction of the ET 0 for the next years demonstrated that the ET 0 values will go up from 2011 to 2113, approximately, for all stations under all three scenarios. This result is in line with the research by Rajabi and Babakhani [32] in Iran and Tiegang et al [33] in China. In conclusion, the highest increase of the ET 0 in the future over Iran will happen from 2080 to 2113 under the A1B scenario, while the lowest will be observed from 2046 to 2079 under the B1 scenario.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The prediction of the ET 0 for the next years demonstrated that the ET 0 values will go up from 2011 to 2113, approximately, for all stations under all three scenarios. This result is in line with the research by Rajabi and Babakhani [32] in Iran and Tiegang et al [33] in China. In conclusion, the highest increase of the ET 0 in the future over Iran will happen from 2080 to 2113 under the A1B scenario, while the lowest will be observed from 2046 to 2079 under the B1 scenario.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, the most critical condition from the aspect of the ET 0 is predicted for the A1B scenario. Rajabi and Babakhani [32] reported the same result. By studying the climate change effect on the ET 0 changes in the west of Iran, they stated that the highest ET 0 rise will happen in the A1B scenario.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations